The Role of Endogenous Timing in Public Goods Provision and Its Implications for Welfare - Jara-Moroni, P (John Wiley and Sons Inc, 2025)
This article analyzes the provision of public goods in a two-player game setting, employing the Game with Observable Delay (GOD) framework to investigate how endogenous timing influences contribution strategies and welfare outcomes. Our analysis shows that, for both symmetric and asymmetric valuation cases, the endogenous timing outcome leads to simultaneous play. This result arises from players strong aversion to the follower position, driven by the leader s free-riding incentives. The outcome is good for welfare, since in both the symmetric and asymmetric cases, simultaneous play leads to greater total contributions compared to the sequential equilibrium. If the framework for contributions was of the Game with Action Commitment type, the outcome would be simultaneous, leading to an inferior welfare result. These findings indicate that fostering environments with a structure akin to the GOD could strategically encourage players to maximize their contributions and improve welfare outcomes in public goods scenarios. © 2025 Wiley Periodicals LLC.